Kepuasan Konsumen Dipengaruhi Oleh Kualitas Pelayanan Studi Pada Perumahan Subsidi Griya Ciroyom Indah - mulia, hari (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research is motivated by the phenomenon of problems related to customer satisfaction in Griya Ciroyom Indah subsidized housing. One of them is from services that are less fast and considered, causing consumer dissatisfaction with residents of Griya Ciroyom Indah subsidized housing. purpose of this study is to determine the description of service quality, description of customer satisfaction and description of the effect of service quality on customer satisfaction. The method used in this research is quantitative method with descriptive and associative approaches. Using data collection techniques with questionnaires to 77 respondents using the sampling method, namely saturated samples. The data analysis technique used in this study uses instruments (validity test and reliability test), correlation coefficient test and determination coefficient test using SPSS version 2. Based on the results of data processing obtained, the instruments used in this study are declared valid and reliable because they have a value greater than r table of 0,224. The value of service quality is 0.730>0.600 and customer satisfaction is 0.744>0.600, so it is declared reliable. The description of service quality with an index value of 3,912 and customer satisfaction with an index value of 2,119 is said to be good. From the results of the product moment correlation coefficient test, there is a